Respuesta :

Answer:

The answer to your question is the letter a

Step-by-step explanation:

 |    1    4    -1   |      |  2    -1   |

 |    3   2    2   |      |  0     3  |         Product  = 2 x 3   and 3 x 2  = 2 x 2

                              | 5     2  |          It is possible to do this product,

                                                      the result will be a 2 x 2 matrix

Process

1.- Multiply first row by first column and second row by second column.

2.- Multiply the second row by the first column and second row by the second column.

  = (1 x 2) + (4 x 0) + (-1 x 5) = 2 + 0 - 5 = -3

  = (1 x -1) + (4 x 3) + (-1 x 2) = -1 + 12 - 2 = 9

  = (3 x 2) + (2 x 0) + (2 x 5) = 6 + 0 + 10 = 16

  = (3 x -1) + (2 x 3) + (2 x 2) = -3 + 6 + 4 = 7

Result

             |  3   9  |

             | 16   7  |    

ACCESS MORE